2019
DOI: 10.1113/jp277727
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term depression of presynaptic cannabinoid receptor function at parallel fibre synapses

Abstract: Key points Inhibition of synaptic responses by activation of presynaptic cannabinoid type‐1 (Cb1) receptors is reduced at parallel fibre synapses in the cerebellum following 4 Hz stimulation. Activation of adenylyl cyclase is necessary and sufficient for down‐regulation of Cb1 receptors induced by 4 Hz stimulation. 4 Hz stimulation reduces Cb1 receptor function by (i) increasing the rate of endocannabinoid clearance from the synapse and (ii) decreasing expression of Cb1 receptors. Abstract Cannabinoid type‐1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 69 publications
(136 reference statements)
0
1
0
Order By: Relevance
“…Purkinje cells synthesize and release endocannabinoids (primarily 2-AG) in response to depolarization of the membrane potential and subsequent calcium influx [44] and/or following activation of type 1 metabotropic glutamate receptors in dendritic spines [45]. Several studies, and our own data, have shown that release of endocannabinoids from Purkinje cell dendrites is sufficient to activate CB1 receptors expressed in presynaptic terminals and inhibit release of neurotransmitters (Fig 3) [ [5][6]46]. Given that CB1 and CB2 receptors both bind 2AG with relatively high affinity [47,48], it is somewhat surprising that depolarization of Purkinje cells and mobilization of endocannabinoids does not activate CB2 receptors in our experiments.…”
Section: Cannabinoid Signaling In Cerebellummentioning
confidence: 99%
“…Purkinje cells synthesize and release endocannabinoids (primarily 2-AG) in response to depolarization of the membrane potential and subsequent calcium influx [44] and/or following activation of type 1 metabotropic glutamate receptors in dendritic spines [45]. Several studies, and our own data, have shown that release of endocannabinoids from Purkinje cell dendrites is sufficient to activate CB1 receptors expressed in presynaptic terminals and inhibit release of neurotransmitters (Fig 3) [ [5][6]46]. Given that CB1 and CB2 receptors both bind 2AG with relatively high affinity [47,48], it is somewhat surprising that depolarization of Purkinje cells and mobilization of endocannabinoids does not activate CB2 receptors in our experiments.…”
Section: Cannabinoid Signaling In Cerebellummentioning
confidence: 99%